Sea Turtle Epibiosis: Global Patterns and Knowledge Gaps - Robinson, Nathan J.; Pfaller, Joseph B. (Frontiers in Ecology and Evolution, 2022)
Competition for space drives many marine propagules to colonize the external surfaces of other marine organisms, a phenomenon known as epibiosis. Epibiosis appears to be a universal phenomenon among sea turtles and an extensive body of scientific literature exists describing the epibiont species found on sea turtles. When viewed in isolation, however, these “species lists” provide limited insights into the factors driving patterns in taxonomic diversity on a global scale. We conducted an exhaustive literature review to collate information on sea turtle-epibiont interactions into a global database. As studies involving meio- and micro-epibionts, as well as plants, are limited, we exclusively focused on animal, macro-epibionts (>1 mm). We identified 304 studies that include a combined total of 1717 sea turtle-epibiont interactions involving 374 unique epibiont taxa from 23 Higher Taxon categories (full Phylum or select phyla differentiated by Subphylum/Class/Subclass). We found that loggerhead turtles hosted the highest taxonomic richness (262 epibiont taxa) and diversity, including representative taxa from 21 Higher Taxon categories, followed by hawksbill, green, olive ridley, leatherback, Kemp’s ridley, and flatback turtles. Nevertheless, the taxonomic richness for all turtle species except leatherbacks was projected to increase with additional studies. We found that taxonomic richness not only varies between species but also between well-studied populations of loggerhead turtles. Lastly, we assessed biases in the current literature and identified knowledge gaps for certain species (e.g., Kemp’s ridleys and flatbacks), life stages (e.g., juveniles), habitats (e.g., oceanic habitats), and geographic regions (e.g., central Pacific, east Atlantic, and east Indian oceans). Our hope is that this database will serve as a foundational platform for future studies investigating global patterns of the diversity, ecological function, and evolutionary origins of sea turtle epibiosis.